Differences in The Emotional Regulation of Male and Female Students - Ocha Lovensa Zonya; Afrizal Sano (Universitas Negeri Padang, 2019)
This research is motivated by students who have unstable emotions and emotions that are exaggerated and incorrect. The purpose of this study is to describe the emotional regulation of male students, describe the emotional regulation of female students, and test whether there are differences in the emotional regulation of male and female students. This research is descriptive and comparative in nature, with 118 VII grade VII and VIII grades of SMPN 4 Padang research. The research instrument used is the Likert scale. Data were analyzed using descriptive statistical techniques and t-test with SPSS version 20 support. The research findings showed that (1) male students had emotional regulation in the medium category (2) female students had emotional regulation in the low category (3 ) there are differences in the emotional regulation of male and female students